Scenarios toolkit - Leney, Tom [Verfasser]; Coles, Mike [Verfasser]; Grollman, Philipp [Verfasser]; Vilu, Raivo [Verfasser] (Office for Official Publications ot the European Communities, 2004)
This toolkit and manual is intended for practitioners involved in the planning and development of education and training policies, new measures and strategies. Scenarios can be developed and applied at several levels. This toolkit will provide illustrations of how scenarios can be used in a range of contexts: international (at a global or European level); in national systems; at regional or sectoral level (in an industry such as transport); and, at the level of a single institution or organisation such as a government agency, school or college. At each level, the chara teristics of the scenarios change and the drivers of change often become more specific as the parameters of the application become more local. (BIBB-Doku)
Keywords: T 3 Forschungsmethoden; I 2.2 Europa; Prognostik; Szenario; Methode; Berufsbildung; Europa